Application of the Myers-Birggs Type Indicator Method in the Member Personality Test Application (Case Study: Bengkulu Regional Police Mobile Brigade Corps) - Putra, Oktian Dwi Pradana; Khairil, Khairil; Beti , Ilayati (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
The Bengkulu Police Mobile Brigade Corps conducts a personality test every year for members which is used as a basis for determining the personality of members. However, so far the implementation is still done conventionally and not computer-based, so it takes quite a long time to get the personality test results for these members. The application of the Myers-Birggs Type Indicator Method to the member personality test application at the Bengkulu Regional Police Mobile Brigade Corps can make it easier for members to carry out personality tests and find out the results of each member's personality test more quickly and accurately. Based on the black box testing that has been done, the results show that the functionality of the member personality test application at the Bengkulu Regional Police Mobile Brigade Corps is running as expected and the application is able to display the personality test results for each member based on personality type from the Myers-Birggs Type Indicator Method